EFFICACY AND TOLERABILITY OF LEVETIRACETAM (KEPPRA®) IN THE TREATMENT OF EPILEPSY: REVIEW OF LITERATURE - K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии, 2015)
In spite of substantial progress in epileptology, complete seizure control cannot be achieved in a considerable proportion of patients (about 30 %); in this regard, the synthesis of new antiepileptic drugs (AEDs) and rational combinations of available AEDs in view of their mechanisms of action remains relevant. Of particular interest are drugs with different mechanisms of action in relation to other AEDs (these drugs include levetiracetam, lacosamide, perampanel, etc.). The authors provide a literature review dealing with one of the new drugs – levetiracetam (Keppra) that has a different mechanism of action, as compared with other AEDs. Levetiracetam has been approved for use as initial monotherapy for partial-onset epilepsy with or without secondary generalization in patients who are at least 16 years of age, as adjunctive treatment of partial-onset seizures with and without secondary generalization in babies who are at least 1 month old (oral solution) or in children who are at least 6 years old (tablets), and in patients who are at least 12 years of age as adjunctive treatment of myoclonic seizures in juvenile myoclonic epilepsy and as therapy for generalized tonic-clonic seizures in idiopathic generalized epilepsy. The review details the mechanism of action of levetiracetam, its pharmacokinetics, and data on its efficacy and tolerability in the treatment of epilepsy. The findings have led to the conclusion that levetiracetam is a well-studied and promising drug used in the monoand polytherapy of different forms of epilepsy.